Characterization of physiological races of Pyricularia grisea in temperate agro-ecosystem of Kashmir, India - ANWAR, ALI; TELI, M.A.; BHAT, G.N.; PARRAY, G.A.; WANI, S.A. (Indian Phytopathology, 2011)
An intensive and stratified survey revealed that all the rice production zones of Kashmir were affected with leaf blast disease in variable severity range of 3.7 – 41.3 per cent whereas highest nodal blast was encountered in Kulgam (7.3%) followed by Khudwani (5.4%) and Larnoo (3.8%) zones of district Anantnag. The most destructive phase of neck blast severity was encountered in every surveyed district with range of 0.3-4.9 percent. Local coarse grain cultivars viz. Safed China, Jhelum and Chenab exhibited susceptibility to the leaf blast but plants largely killed due to devastating occurrence of blast in Mushk Budgi, Khutch and Kamad cultivars. During the survey, six hundred twenty monoconidial isolates (MI) of rice blast pathogen (Pyricularia grisea) were developed from different parts of Kashmir valley and tested for race spectrum first time in temperate conditions of Kshmir region in India viz., ID-1, ID-2, IC-17, IC-25 and IB-4. A maximum of three races viz. ID-1, ID-2 and IC-17 were appeared from district Anantnag which is a bowl of rice in Kashmir. Race ID-1 and IC-17 were recorded in the valley with higher frequency occurrence of 28.54 and 34.19 per cent respectively followed by IC-25 with 18.39 per cent. Race IB-4 and ID- 2 were also found to be present with 12.42 and 6.45 per cent respectively